2021
DOI: 10.1590/fst.15720
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of ultrasound pretreatment time and microwave power level on drying and rehydration kinetics of green olives

Abstract: In this study, the effect of ultrasound (US) combined microwave (MW) drying of green olive slices was studied. Olive samples were exposed to ultrasound (5 and 10 minutes; 32 KHz) at room temperature before dried at microwave at 3 different power level (180W, 450 W and 800 W). The drying and rehydration characteristics and quality parameters of olives were determined by comparing with obtained by non-ultrasound pretreated MW dried samples. Midilli et al.and Diffusion models were the most suitable models for US-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 27 publications
0
18
0
2
Order By: Relevance
“…Total phenolic compounds (TPC) were determined according to the method of Sun et al (2005) with minor modifications (Aydar, 2020;Lu et al, 2011). In this method, Folin-Ciocalteu reagent was diluted with distilled water to prepare ten-time dilutions.…”
Section: Total Phenolic and Flavonoid Contentsmentioning
confidence: 99%
“…Total phenolic compounds (TPC) were determined according to the method of Sun et al (2005) with minor modifications (Aydar, 2020;Lu et al, 2011). In this method, Folin-Ciocalteu reagent was diluted with distilled water to prepare ten-time dilutions.…”
Section: Total Phenolic and Flavonoid Contentsmentioning
confidence: 99%
“…Microwave power level shortened the rehydration time of samples can be shown in Figure 3. It was reported that increasing microwave power up to 800 W in 5 and 10 minutes ultrasound pretreated olive samples caused lower rehydration capacity of dried samples (Aydar, 2021). This might be ascribed to the fact that higher microwave power levels enhances the molecular diffusion rate due to increase of temperature.…”
Section: Resultsmentioning
confidence: 98%
“…However there are limited numbers of studies investigates the combine effect of microwave and ultrasound technologies during drying of foods. Recently, an ultrasound pretreatment time of up to 10 minutes has been investigated in drying olives (Aydar, 2021), but the effect of higher ultrasound treatment time in an ultrasonic bath with lower concentration has not been studied in previous studies. Peleg's model was also successfully applied to describe rehydration/hydration behavior of foods including carrot (Planinic et al,2005), cowpea (Yildirim and Atasoy, 2017) and chickpea (Yildirim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Son yıllarda ürün/su konsantrasyon etkisinin araştırıldığı çalışmalar da yapılmaktadır. Yapılan çalışmalara bakıldığında ürün:su oranı (ağırlık:ağırlık) kurutulacak gıdaya ve diğer çalışma parametrelerine göre değişmekle beraber 5-10 dakikalık ultrason uygulamalarında 1:4 ve 1:5 oranlarının, daha yüksek sürelerde uygulanan ultrason ön işlemlerinde (≥15 dakika) ise bu oranın 1:9 olarak uygulanabileceği belirlenmiştir (Aydar, 2020b;Aydar 2021;Nowacka ve Wedzik, 2016).…”
Section: (2): 1165-1175 2021unclassified